Effects of Lactobacillus fermentation on Eucheuma spinosum polysaccharides: Characterization and mast cell membrane stabilizing activity. (15th June 2023) - Zhang, Jun; Liu, Qingmei; Gu, Fudie; Liu, Yan; Zhou, Yu; Li, Yan; Chen, Huiying; Liu, Hong; Xiao, Anfeng; Liu, Guangming
Abstract: Eucheuma polysaccharides have varieties of biological activities. However, it is accompanied by problems like large molecular weight, high viscosity, and low utilization. Here, we first prepared fermented Eucheuma spinosum polysaccharides (F-ESP) by Lactobacillus fermentation, compared with low-temperature freeze-thaw ESP (L-ESP) prepared by the freeze-thaw method, explored the composition and structural characteristics of F-ESP and L-ESP, and evaluation of the ability of different samples to inhibit mast cell degranulation using classical mast cell model. Then, the activity of L-ESP and F-ESP in vivo was preliminarily evaluated using a passive cutaneous anaphylaxis model. Two kinds of F-ESP named F1-ESP-3 and F2-ESP-3 were obtained by fermentation of Eucheuma spinosum with the selected strains of Lactobacillus.sakei subsp.sakei and Lactobacillus.rhamnosus . Compared with the purified component L-ESP-3, the monosaccharide composition of F1-ESP-3 contains more glucuronic acid, the molecular weight reduced from >600 kDa (L-ESP-3) to 28.30 kDa (F1-ESP-3) and 33.58 kDa (F2-ESP-3), F1-ESP-3 has higher solubility and lower apparent viscosity. Fermentation did not destroy the functional groups and structure of ESP. Moreover, F1-ESP-3 significantly inhibited RBL-2H3 cell degranulation by reducing depolymerization of F-actin and Ca 2+ influx. F1-ESP-3 reduced the symptoms of mast cell-mediated passive cutaneous anaphylaxis, indicating that F1-ESP-3 may have better anti-allergic activity in vivo . Graphical abstract: Unlabelled Image